Sistem Penunjang Keputusan Berbasis Aplikasi Java Pada Proses Produksi Pembibitan Benih Ikan Air Tawar di Desa Talang Kemulun - Rosy Dasmita (ITP Press, 2022)
The Talang Kemulun Local Fish Seed Center (BBI) is one of the structural work units that assist the Kerinci District Fisheries Service in implementing fisheries development, especially in meeting the needs of fish seeds. The freshwater fish fry production process at the Talang Kemulun Local Fish Seed Center (BBI) is dominated by carp, semah, red tilapia, black tilapia, medic, koan, and betok. These species account for more than 80%, with approximately 7,250,000 fish from the total freshwater fish production, but due to the changing demand differences, farmers in the freshwater fish breeding production process must always consider the types of fish that are profitable in the process of fish seed production. This research is implemented with a Java application program used to design a decision support system to determine the type of freshwater fish that is suitable for the production process of freshwater fish species. The results show that the designed system can help fish farmers determine which fish types are suitable for seed breeding production. Keywords- Decision Making System, Java, Fish Breeding